A Diet-Induced Pediatric Model of Non Alcoholic Fatty Liver Disease Using Neonatal Iberian Pigs (OR26-02-19). (13th June 2019) - Hernandez, Gabriella; Smith, Victoria; Temple, Mieko; Bennet, Darin; Columbus, Daniel; Rice, Margaret; Burd, Matthew; Sprayberry, Kim; Edwards, Mark; Peterson, Daniel; Fanter, Rob; Kitts, Christopher; et al.
Abstract: Objectives: The prevalence of non-alcoholic fatty liver disease (NAFLD) in children has increased over the past decades, creating a need for animal models that recapitulate the features of the pediatric disease. Iberian pigs have a leptin-resistant phenotype characterized by hyperleptinemia, hyperphagia, and extreme adipogenesis. We hypothesized that neonatal Iberian pigs fed a high-fat high-fructose (HFF) diet will develop a pattern of liver injury resembling pediatric NAFLD. In addition, we sought to determine if a mixture of probiotics would prevent the disease. Methods: Animals were fed 1 of 4 diets containing (g/kg body weight × d) 0 g fructose, 11 g fat and 199 kcal (CON-N; n = 8), 22 g fructose, 16 g fat and 300 kcal (HFF-N; n = 6), CON + probiotic (CON-P; n = 6), or HFF + probiotic (HFF-P; n = 6) every 6 h for 70 d. The probiotic mixture (6.2 × 10 4 cfu/mL) contained Pediococcus, Lactobacillus and Bacillus. Body weight was recorded every 3 d. Serum markers of liver injury and dyslipidemia were measured on d 65 at 2 h post feeding. Fasting leptin, insulin, glucose and homeostatic model assessment (HOMA) values were assessed on d 70. Liver tissue was collected on d 70 for histology, triacylglyceride (TG) quantification, and gene expression of tumor necrosis factor (TNF) α, tumor growth factor (TGF) β, interleukin (IL) 1α, peroxisome proliferator-activated receptor (PPAR) γ, carbohydrate-responsive element-binding protein (ChREBP) and sterol regulatory element-binding protein (SREBP) 1c. Results: Body weight was higher in CON-P, and insulin and HOMA values in HFF-P and CON-P (P ≤ 0.05). Leptin, alanine and aspartate aminotransferases, alkaline phosphatase, lactate dehydrogenase and total bilirubin were increased ( P ≤ 0.001), and high and low density lipoproteins decreased ( P ≤ 0.05) in HFF-N and HFF-P. Livers in HFF-P and HFF-N had higher relative weight and TG ( P ≤ 0.001), micro and macrovesicular steatosis, ballooning degeneration, Mallory-denk bodies, inflammation and necrosis, increased gene expression of TNFα, TGFβ, IL1α and PPARγ ( P ≤ 0.001), and decreased ChREBP ( P ≤ 0.001). Conclusions: Iberian pigs fed a HFF diet recapitulate many pediatric NAFLD-associated features, in the absence of obesity and independently of probiotic supplementation, suggesting a potentially suitable model for pediatric NAFLD research. Funding Sources: ARI, AcornSeekers.